Printability analysis in additive manufacturing. Issue 3 (4th May 2018) - Corcodel, Radu I.; Ilies, Horea T.
ABSTRACT: In recent years Additive Manufacturing (AM) has advanced from design and fitting validation to biomedical, rapid tooling, tissue engineering, the arts and even food manufacturing. The corresponding scale reduction did not coincide with improving two of the most important process characteristics, namely print accuracy and build time. In this paper we introduce a computational framework for computing the maximum build volume for given non-circular extruders and printing machines that have 2, 3 and perhaps higher number of degrees of freedom (DOF). The proposed method also outputs the accessible configuration space of a multi-DOF AM machine that is instrumental in planning the final (temporal) motion of single or multiple print heads. Furthermore, we show that the proposed method allows the ranking of multiple extruders based on their volumetric deviation from nominal geometry. This formulation makes no assumption about the number of machine DOFs, nor about the planarity of the target contour, making it applicable to emerging AM technologies such as 6-axis printing with non-planar layers, and layer-less additive manufacturing. GRAPHICAL ABSTRACT: